Industrial training report: UniKL MIIT - Shamsudin, Muhamad Luqman Nurhakim (Universiti Teknologi MARA, Perlis, 2024)
An internship is a role in which a student or trainee collaborates with an organization to acquire practical work experience or fulfil criteria for a qualification. Internships offer students a valuable opportunity to acquire new skills relevant to their chosen career, facilitate adaptation to the professional work environment, and open up potential career paths. In Malaysia, commonly referred to as industrial training, internships typically span a duration of 3 to 6 months, and they are often obligatory for students in their final year of study. This executive summary encloses the pivotal aspects of my internship at UniKL MIIT over the spent of 6 months from 2 October 2022 until 10 March 2024. Engaging in diverse projects, I undertook responsibilities that significantly contributed to my professional development. After spending 6 months at UniKL MIIT, I took some time to analyse the organization using a Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis. For each category, I have highlighted two key findings that stood out based on my experiences. Collaborating with a diverse team throughout the internship enhanced my teamwork and communication skills. This executive summary serves as a concise overview, emphasizing the practical application of skills, the utilization of SWOT analysis, and the positive influence of the internship on both personal and professional growth.